2019
DOI: 10.1016/j.bja.2018.11.028
|View full text |Cite|
|
Sign up to set email alerts
|

Retrospective analysis of 30-day unplanned readmission after major abdominal surgery with reversal by sugammadex or neostigmine

Abstract: Background: Sugammadex is associated with fewer postoperative complications, but its impact on 30-day unplanned readmission is unclear. Methods: This was a single-centre retrospective observational study of patients after major abdominal surgery between 2010 and 2017, where rocuronium was the only neuromuscular blocker used. The primary endpoint was the difference in incidence of 30-day unplanned readmission between reversal with sugammadex or neostigmine. The secondary endpoints were the length of hospital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 32 publications
3
43
1
Order By: Relevance
“…9e12 Recent evidence suggests that the use of sugammadex may be associated with shorter hospital length of stay (LOS) and reduced hospital readmission after some major abdominal surgeries; however, additional research is needed to determine whether these findings are generalisable to other patient populations. 13 Elderly patients undergoing robotic prostatectomy may particularly benefit from reversal of neuromuscular block with sugammadex compared with neostigmine. 14 Compared with the general population, elderly patients have a higher incidence of postoperative pulmonary complications from residual neuromuscular block.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…9e12 Recent evidence suggests that the use of sugammadex may be associated with shorter hospital length of stay (LOS) and reduced hospital readmission after some major abdominal surgeries; however, additional research is needed to determine whether these findings are generalisable to other patient populations. 13 Elderly patients undergoing robotic prostatectomy may particularly benefit from reversal of neuromuscular block with sugammadex compared with neostigmine. 14 Compared with the general population, elderly patients have a higher incidence of postoperative pulmonary complications from residual neuromuscular block.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…18 These complications could in part explain why patients with residual neuromuscular block demonstrate an increase in ICU admission rate and prolonged hospital length of stay, 19 and increased rates of readmission among ambulatory patients. 7 The findings of Oh and colleagues 4 are interesting and thought provoking in this context.…”
Section: Methodological Issues In Observational Studies Of Readmissiomentioning
confidence: 92%
“…1 There are several scenarios where readmissions might be missed. In the context of the study by Oh and colleagues, 4 uncaptured readmissions occur when complications associated with the use of neuromuscular reversal agents are treated in other hospitals far away from the study site. Mortality can also affect the rate of readmission, as patients who died would no longer be at risk for readmission.…”
Section: Methodological Issues In Observational Studies Of Readmissiomentioning
confidence: 99%
See 1 more Smart Citation
“…First, PORC and NMBA reversal with high-dose neostigmine is known to be associated with development of hypopharyngeal weakness [30,31], which could lead to a risk of aspiration and pneumonia, and overall higher rates of PPCs [26,32,33]. Furthermore, we recently published an observational study in which we showed that NMBA reversal by sugammadex was associated with lower 30-day unplanned readmission rates, hospital charges, and length of hospital stay after major abdominal surgery [34]. In this study, we showed that reversal by sugammadex, which might be closely related to reduced PORC, could have relatively long-term effects on outcome, beyond the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%